Charcot–Marie–Tooth Disease type 4C: Novel mutations, clinical presentations, and diagnostic challenges. Issue 5 (24th October 2017) - Jerath, Nivedita U.; Mankodi, Ami; Crawford, Thomas O.; Grunseich, Christopher; Baloui, Hasna; Nnamdi‐Emeratom, Chioma; Schindler, Alice B.; Heiman‐Patterson, Terry; Chrast, Roman; Shy, Michael E.
ABSTRACT: Introduction: This study analyzes and describes atypical presentations of Charcot–Marie–Tooth disease type 4C (CMT4C). Methods: We present clinical and physiologic features of 5 patients with CMT4C caused by biallelic private mutations of SH3TC2 . Results: All patients manifested scoliosis, and nerve conduction study indicated results in the demyelinating range. All patients exhibited signs of motor impairment within the first years of life. We describe 2 or more different genetic diseases in the same patient, atypical presentations of CMT, and 3 new mutations in CMT4C patients. Discussion: A new era of unbiased genetic testing has led to this small case series of individuals with CMT4C and highlights the recognition of different genetic diseases in CMT4C patients for accurate diagnosis, genetic risk identification, and therapeutic intervention. The phenotype of CMT4C, in addition, appears to be enriched by a number of features unusual for the broad CMT category. Muscle Nerve 57 : 749–755, 2018